(untitled) (Applied Biological Research, 2023)
Plant seed proteins have pivotal health benefits. However, diminutive information is available on the presence of total soluble protein (TSP) levels in major crops. The present study was aimed to extract total soluble proteins from seven species/varieties of Mucuna and evaluate their activity for endogenous regulation of proteases. The total soluble proteins and protease inhibitory activity of various varieties/species of Mucuna were studied by both qualitative and quantitative methods. The total soluble proteins isolated were variable (18 to 29%) with maximum proteins in Mucuna utilis (29%) and minimum in M. pruriens V1 (18.7%). The total protease inhibitory activities were in the range of 9-18.25 TIU mg-1 with maximum in M. pruriens (18.25 TIU mg-1) and minimum in M. pruriens V1 (9.78 TIU mg-1). The TSP content and protease inhibitory activities in other species/varieties were: M. pruriens 27.4% and 18.25 TIU mg-1, M. utilis 29% and 16.67 TIU mg-1, M. monosperma 26.9% and 15.27 TIU mg-1, M. pruriens V2 21.7% and 13 TIU mg-1, M. hirsute 23.8% and 15.93 TIU mg-1 and M. gigantea 24.3% and 11.98 TIU mg-1, respectively. Electrophoretic analysis revealed the presence of various trypsin isoinhibitors and multiple protein bands. The present analysis revealed that Mucuna seeds can be used as an alternative to protein source and their biological activity indicated their usefulness in medical field.